EYE DISEASE DETECTION WITH DEEP LEARNING MODELS SUPPORTED BY THE CBAM ATTENTION MECHANISM - Coşkun, Rıdvan; Kaya, Duygu; Güler, Hasan (My University, 2025)
Early diagnosis of eye diseases plays a critical role in treatment success and public health. With the widespread use of modern medical imaging methods, the development of automated diagnostic systems from retinal fundus images has become an important research area. In this study, the effects of integrating the Convolutional Block Attention Module (CBAM) into EfficientNetB0 and DenseNet121 architectures were investigated for the classification of cataract, diabetic retinopathy, glaucoma, and healthy subjects. Experimental results demonstrated that the CBAM attention mechanism enhances accuracy and generalization performance, particularly in distinguishing complex retinal findings. For DenseNet121, accuracy, precision, recall, and F1-score were obtained as 88.37%, 89.66%, 88.37%, and 88.52%, respectively. EfficientNetB0 achieved 96.32% accuracy, 96.34% precision, 96.32% recall, and 96.33% F1-score. After CBAM integration, the accuracy of DenseNet121 increased to 90.39% and its F1-score to 90.54%, while EfficientNetB0 improved to 96.56% accuracy and 96.57% F1-score. These results reveal that the incorporation of CBAM enhances the performance of deep learning models and significantly contributes to the development of reliable and clinically applicable systems for the automated detection of eye diseases
Keywords: Deep Learning; CBAM; Attention Mechanism; Retinal Fundus Imaging; Eye Disease Classification